2015
DOI: 10.15835/nbha.43.2.10048
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficiency of Edible Films in Food Industry

Abstract: In the current article, several applications of materials in food packaging and food safety are reviewed, including: polymers as high barrier packaging materials, natural substances as potent antimicrobial agents, and the efficiency of antimicrobial films in food industry. The first condition of all this materials in order to be utilised in food industry is to fall into the list of generally accepted as food grade. Active antimicrobial food packaging systems are supposed not only to passively protect food prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…The final reversed-phase HPLC step of the purification procedure led to isolation of a single active fraction having antibacterial activity. Bioautography on thinlayer chromatograms, a method previously used for detecting antibacterial and antifungal substances for control of pathogens was useful to revel the active fraction [34]. The study indicated that the isolated Lactobacillus species meet several of the criteria for use as a probiotic.…”
Section: Qualitative Analysis Of Antimicrobial Compounds By Tlcmentioning
confidence: 99%
“…The final reversed-phase HPLC step of the purification procedure led to isolation of a single active fraction having antibacterial activity. Bioautography on thinlayer chromatograms, a method previously used for detecting antibacterial and antifungal substances for control of pathogens was useful to revel the active fraction [34]. The study indicated that the isolated Lactobacillus species meet several of the criteria for use as a probiotic.…”
Section: Qualitative Analysis Of Antimicrobial Compounds By Tlcmentioning
confidence: 99%
“…Ideal candidates for reducing the huge amount of conventional plastics are the "bioplastics, manufactured exclusively with natural polymers, which are able to be fully 2 of 10 recycled into the environment, in a short time, following their utilization as packaging materials" [2][3][4]. Renewable resources for producing bioplastics are represented by several polysaccharides (PSs) that are able to constitute the matrices for edible films and coatings [5,6]. Nevertheless, films based on natural polymers are widely known to exhibit poor mechanical resistance, as well as limited barrier and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The present-day accelerated lifestyle has increased the production and consumption of minimally processed horticultural and ready-to-eat products [1][2][3]. However, the development of fresh-cut products from fruits such as pineapple, papaya, watermelon, mango, and cantaloupe, among others, has been limited because these foods are highly perishable compared to intact fruit.…”
Section: Introductionmentioning
confidence: 99%